2020
DOI: 10.1093/jas/skaa083
|View full text |Cite
|
Sign up to set email alerts
|

Cricket (Gryllodes sigillatus) meal fed to healthy adult dogs does not affect general health and minimally impacts apparent total tract digestibility

Abstract: Insects can serve as a novel high-quality protein source for pet foods. However, there is an absence of research investigating the use of insects in pet food. The study objective was to evaluate the apparent total tract digestibility and possible health effects of diets containing graded levels of cricket (Gryllodes sigillatus) meal fed to healthy adult dogs. Thirty-two adult Beagles were randomly assigned to one of four dietary treatments: 0%, 8%, 16%, or 24% cricket meal. Dogs were fed their respective diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 25 publications
5
29
0
Order By: Relevance
“…The latter study also reported that dogs fed kibbles coated with 2.5 or 5% BSFL oil consumed 91.5 and 116.2% of their metabolisable energy requirements, respectively. Including 8, 16 or 24% banded cricket (Gryllodes sigillatus) meal in extruded foods did not affect food intake in dogs (n=8) (Kilburn et al, 2020).…”
Section: Palatabilitymentioning
confidence: 89%
See 3 more Smart Citations
“…The latter study also reported that dogs fed kibbles coated with 2.5 or 5% BSFL oil consumed 91.5 and 116.2% of their metabolisable energy requirements, respectively. Including 8, 16 or 24% banded cricket (Gryllodes sigillatus) meal in extruded foods did not affect food intake in dogs (n=8) (Kilburn et al, 2020).…”
Section: Palatabilitymentioning
confidence: 89%
“…Meyer et al (2019) estimated that the apparent faecal N digestibility of their BSFL meal was 83.1% when included in an extruded food and 83.4% when included in a pelleted food. Feeding dogs extruded foods with 8, 16 or 24% inclusion of banded crickets resulted in apparent faecal N digestibility values of 84.8, 86.0 and 82.1%, respectively (Kilburn et al, 2020). The average apparent faecal N digestibility of commercial dog foods can be considered to be close to 80% (Daumas et al, 2012;Hendriks et al, 2013;Hervera, 2011;Kendall et al, 1982), suggesting that the insect meals are in the range of conventional protein sources.…”
Section: Nutritional Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, insects have potential as alternative protein sources for animals, particularly dogs. Based on several study reports, dogs have been shown to be able to consume diets containing black soldier fly (Hermetia illucens) larvae [6][7][8][9][10][11], tropical house cricket (Gryllodes sigillatus) [12], housefly (Musca domestica) larvae, lesser mealworm (Alphitobius diaperinus) [6], and yellow mealworm (Tenebrio molitor) [6,7] without adverse effects on health or nutrient digestibility, even if used as almost total replacements for common protein sources [6]. House cricket (Acheta domesticus: AD) and mulberry silkworm (Bombyx mori: BM) pupae are other potential insects able to be produced on a large scale.…”
Section: Introductionmentioning
confidence: 99%